Analisis Pengendalian Persediaan Produk Dengan Metode Economic Order Quantity (EOQ) Menggunakan Framework Laravel - sanjaya, fedo; Diana; Yulia Darmi; Mutahanah (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2023)
The importance of managing stock makes it one of the processes that determine performance efficiency and maximize company income. In the process of determining the stock of goods requires sales data as well as the cost of the process of ordering and storing goods. The process of determining the stock of goods is not easy because many factors are calculated at once so it requires the help of a computer to be able to provide fast and precise conclusions. The method commonly used in maximizing the process of determining stock of goods is the Economic Order Quantity (EOQ) method. The goal is to produce the most efficient amount of stock to optimize the company's needs so that it can meet customer needs. This butinara store wants to apply the concept of control of the inventory of goods ordered at an optimal minimum cost. With the development of this goods supply application, it can later become a source or reference in the world of sales so that it can be used as a lesson for technological developments